Analysis of Impact Contract Change Order (CCO) on Time & Cost (Case Study : Counterweight and Tano Ponggol’s Channel Project in Samosir Regency) - LARASATI, ENDAH; SHOLIKIN, YUDHA ALFANDA MUHAMMAD; KRISTIAWAN, AGUNG (Science and Technology Research Centre, Universitas PGRI Semarang, 2025)
In many projects, changes often occur due to on-site conditions. These changes are made to ensure that the work can be carried out properly and in accordance with actual field requirements. Typically, such changes—whether additions, reductions, or replacements—lead to modifications in the contract documents. These modifications result in a Contract Change Order (CCO), which can affect several aspects of the project.This study aims to analyze the impact of Contract Change Orders (CCOs) on project duration and cost, using the Counterweight and Tano Ponggol Channel Project in Samosir Regency as a case study. The results of the study indicate an increase in project duration by 175 days. In terms of cost, the CCO led to a reduction in the counterweight work budget from IDR 25,018,491,000 to IDR 18,768,883,000.